1993
DOI: 10.1007/bf02602965
|View full text |Cite
|
Sign up to set email alerts
|

New retrievable percutaneous vena cava filter: Experimentalin vitro andin vivo evaluation

Abstract: A new retrievable percutaneous vena cava filter was tested in vitro and in vivo in 15 foxhounds. In vitro, the new vena cava filter was compared with the standard Kimray-Greenfield filter and the Günther basket filter. The new filter is a stainless steel half-basket filter and is suitable for percutaneous antegrade or retrograde insertion through a 8.5 Fr introducer sheath. In vitro testing showed the filter causing no significant flow alterations and being highly effective in capturing medium- and large-sized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
5

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 9 publications
2
28
0
5
Order By: Relevance
“…In a previous study, 1 of 11 filters implanted in dogs was irretrievable by 2 weeks after implantation because they were firmly adhered to the vessel wall. 32 The venographic profile of the irretrievable filters in the present study also indicated that the hook of the filter was attached to the vein wall. Among 6 cases of retrieval failure, 2 patients were imaged by intravascular ultrasound to reveal the reason for the unsuccessful retrieval and in each case the filter's hook was found to be attached to the IVC wall and high-intensity echograms revealed fibrin deposits around the hook (Fig 3).…”
Section: Discussionsupporting
confidence: 68%
“…In a previous study, 1 of 11 filters implanted in dogs was irretrievable by 2 weeks after implantation because they were firmly adhered to the vessel wall. 32 The venographic profile of the irretrievable filters in the present study also indicated that the hook of the filter was attached to the vein wall. Among 6 cases of retrieval failure, 2 patients were imaged by intravascular ultrasound to reveal the reason for the unsuccessful retrieval and in each case the filter's hook was found to be attached to the IVC wall and high-intensity echograms revealed fibrin deposits around the hook (Fig 3).…”
Section: Discussionsupporting
confidence: 68%
“…In vitro experiments have demonstrated that 100% and 95% of emboli 5 mm in diameter are trapped by the AF and the TF, respectively [7,8], whereas the GtF could capture 92% of clots 2-4 mm in diameter [13]. In contrast, a 40% failure rate with 5 • 10 mm clots was reported for the GF by Neuerburg et al [6]. The SF, GtF, FF, PF, and NF can be inserted through a narrow-caliber sheath [1,2,9,10].…”
Section: Discussionmentioning
confidence: 86%
“…Neither has this problem been encountered with the other nitinol retrievable filter described in the literature [10]. Both the AF and the GF retain the potential to tilt after deployment [6,7]. Though function may not be affected in the off-axis position [7], the retrieval hook is likely to abut against the vessel wall in this position making snaring prior to removal difficult [8].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations